Strategic Resource Expansion for Clean Energy Transition in the UAE - Aldarmaki, Nasser Rashed Obaid (2026)
A Master of Science thesis in Electrical Engineering by Nasser Rashed Obaid Aldarmaki entitled, “Strategic Resource Expansion for Clean Energy Transition in the UAE”, submitted in April 2026. Thesis advisor is Dr. Ahmed Osman and thesis co-advisor is Dr. Mostafa Shaaban. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).